PENTINGNYA SUPERVISI UNTUK PENGEMBANGAN STAFF DI MADRASYAH IBTIDAIYAH MUHAMMADIYYAH JUWIRAN KLATEN - Meti Fatimah; Ainun Mardhiyah; Ismi Nur Azizah (Institut Islam Mamba'ul 'Ulum Surakarta, 2021)
The purpose of this study was to determine the importance of supervision of staff development at Madrasyah Ibtidayyah Muhammadiyah Juwiran Klaten. The type of research used is descriptive qualitative. With the method of collecting data through observation, interviews and documentation. While the data analysis activities are data reduction, data presentation, and drawing conclusions. The results of this study indicate that one way to develop human resources at Madrasyah Ibtidaiyyah Muhammadiyah Juwiran Klaten is by supervision, By improving the quality of education which must start from the aspect of teachers and other education personnel concerning the quality of their professionalism and welfare in a professional education management.